Analysis of Emergency Situations When Working with Pathogenic Biological Agents within the Framework of Risk-Oriented Approach - E. A. Snatenkov; N. P. Ageeva; K. A. Rotov; A. A. Kovalenko (Проблемы особо опасных инфекций, 2022)
The aim – based on the analysis of accidents when working with pathogenic biological agents (PBA) of pathogenicity groups I–II, draw conclusions about the causes of their occurrence and formulate recommendations for improving biological safety measures to reduce the risk of accidents.Materials and methods. The subject of the study was the data on accidents that happened during the work with PBA, stated in protocols of the commission for monitoring compliance with biological safety requirements of the Volgograd Research Anti-Plague Institute over the period of 1986–2020. Assessed were the type of emergency, their number, main causes and prerequisites for occurrence, professional category of a worker who participated in an accident.Results and discussion. During the specified period 3 types of accidents were recorded: accidents with spraying, accidents with skin lesion, accidents without spraying. There were no accidents with damage to the insulating suit and the pneumatic suit during the entire period under investigation. Of the total number of accidents, 42.85 % of cases were associated with skin lesion due to the bite of an experimental animal due to its incorrect fixation during infection, feeding, care, or due to autopsy of animals. Spillage accidents were recorded in 42.85 %; accidents without spraying amounted to 14.2 %. The categories of employees who made the greatest number of accidents have been identified: laboratory assistants – 39.2 % of cases, researcher officers – 14.2 %, disinfectors – 14.2 %. The causes of accidents and the prerequisites contributing to their realization have been pinpointed. The main ways and measures to reduce the risks of emergency situations for personnel when working with pathogens of particularly dangerous infectious diseases are put forward.